Systematic Study of Structural Divisions of Industrial Enterprise Using Queuing Systems - Navatskaya, Veronika; Neyrus , Semyon; Skorobogatova , Maria; Afanasiev , Mikhail (Journal of Technology Management & Innovation, 2023)
In this article we discuss the use of simulation modeling on the example of several enterprises in various industries. An analysis of the work of enterprises is carried out and a simulation model is built on its basis. The results obtained are also evaluated and options for improving the functioning of enterprises are proposed. In other words, the purpose of the work is to study the literature on this topic, analyze and model the work of companies to improve the quality of their functioning.